Analysis of Moral Education Thought from Ibn Miskawaih's Perspective and Its Implications in the Present Time - Rahmadin Munauwarah; Ahmad Arifi; Rachmad Resmiyanto (al-Afkar, Journal For Islamic Studies, 2024)
Seeing the phenomenon of abomination of morality that is rife in today's society, it seems that there has been no attempt to overcome it. Education, which so far has been regarded as a reference in forming a generation of morals, now seems to be in name only, because moral decline does not only occur among the uneducated, but is also widely practiced by students. Even the worst morals also emerge from educational institutions. Therefore the author conducted research by taking the title of the concept of Ibn Miskuwaihi's thoughts about moral education and its relevance to the world of Islamic education in modern times. The research method used by the author uses qualitative descriptive research with a type of literature review, namely research that only focuses on finding the necessary data, focuses on studying the literature, with the aim of being able to find out about the concept of thinker Ibnu . Miskuwaih. in shaping morals, and its relevance to the world of Islamic education in this modern era. The results of this study are three things, first is the concept of ibn Mikuwaih's thought as a guideline that must be upheld by educators, as well as educators to address everything that is demanded in this modern era, secondly moral education is not just improving morals among fellow human beings, but Moral education put forward by Ibn Miskuwaih can also improve morals on the side of Allah SWT who is able to create modern humans with all forms of progress. These three moral educations in their application are not limited by space and time while there are still moral abominations, especially in this modern era where despicable morals are as rampant as in the time of Ibn Miskuwaih.